IDENTIFIKASI VARIABEL PENENTU STRUKTUR MODAL DAN ADJUSTMENT TO TARGET CAPITAL STRUCTURE: TRADE-OFF THEORY - C. Ambar Pujiharjanto; Nilmawati Nilmawati; R. Hendri Gusaptono (University of Merdeka Malang, 2014)
The purpose of this paper was to test the trade-off theory of capital structure. We started with identifyingvariables that influenced capital structure. Partial Adjustment Model used in this study was to test adjustmentto target capital structure. Based on a sample of non-financial Indonesian listed firms from 2008 to 2012, wefound liquidity, profitability, tangible asset, growth, and cash flow influenced the use of debt on the firm. Theresults of the test Speed of Adjustment (SOA) with Partial Adjustment Model showed the inconsistency of theDynamic Trade-Off Theory.